2016
DOI: 10.18632/oncotarget.7199
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CD4+CD25+Foxp3+ cells in peripheral blood in relation to urinary bladder cancer malignancy indicators before and after surgical removal

Abstract: Tumor cells communicate with stromal cells, including cancer-associated fibroblasts (CAFs) and tumor-associated macrophages (TAMs), to form microenvironment inhibiting immune responses. Regulatory T cells (Tregs, CD4+CD25+FoxP3+) stimulate immune tolerance and facilitate tumor progression. We analyzed the changes in Treg frequencies assessed using flow cytometry in the peripheral blood of patients with urothelial bladder cancer before and after tumor-removal. Changes in Treg frequency were investigated in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Increasing the FoxP3+/CD4+ ration of TIL seems to be an independent adverse prognostic factor in a hormone receptor positive group of patients, mainly in a luminal A subtype of breast cancer [21]. Analyses of patients with lung [7], urinary bladder [8] and ovarian cancers [9,10] yielded similar results, confirming the relationship between Treg cell population size and cancer stage.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Increasing the FoxP3+/CD4+ ration of TIL seems to be an independent adverse prognostic factor in a hormone receptor positive group of patients, mainly in a luminal A subtype of breast cancer [21]. Analyses of patients with lung [7], urinary bladder [8] and ovarian cancers [9,10] yielded similar results, confirming the relationship between Treg cell population size and cancer stage.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, it has been proven that in patients with sometypes of cancers (for example, breast [6], lung [7], urinary bladder [8], and ovarian cancers [9,10] the Treg cell subpopulation size correlates withan advanced stage of cancer. However, there is no such correlation with the histological tumor type, for instance, squamous vs adenocarcinoma in patients with lung cancer [7] and mucinous vs serous adenocarcinoma in patients with ovarian cancer [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another trial showed that a low CD4+CD25+FOXP3+ Treg frequency after radical cystectomy in pT2-pT4 tumors was associated with poor survival. The authors think that this post-surgery Treg decrease may indicate a tumor-specific immune tolerance during tumor advancement [41]. Moreover, Tregs can suppress effector mechansims of the immune response in a variety of vaccination models [4244].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated several probable mechanisms of tumor progression by the way of modulating the immune system anti-tumor response. One important mechanism is the suppression of anti-tumor response by an excess infiltration of regulatory T cells (Tregs) [9]. The over-expression of RCAS1 in tumor cells (TCs) and the surrounding cells of the cancer microenvironment were also shown to correlate with clinical and pathomorphological patterns of malignancy [5].…”
Section: Introductionmentioning
confidence: 99%